Global Dynamical Systems Involving Generalized 𝑓-Projection Operators and Set-Valued Perturbation in Banach Spaces - Yun-zhi Zou; Xi Li; Nan-jing Huang; Chang-yin Sun (Journal of Applied Mathematics)
A new class of generalized dynamical systems involving generalized f-projection operators is introduced and studied in Banach spaces. By using the fixed-point theorem due to Nadler, the equilibrium points set of this class of generalized global dynamical systems is proved to be nonempty and closed under some suitable conditions. Moreover, the solutions set of the systems with set-valued perturbation is showed to be continuous with respect to the initial value.